Investigation of collection method of retail loan encompassing risk management in City Bank Ltd. - Rafat, ASM Rubayet Hossain (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.